TINJAUAN YURIDIS PERTIMBANGAN ALAT BUKTI BERUPA KETERANGAN AHLI DALAM MEMUTUSKAN PERKARA DI PENGADILAN - Rudi Antonius Panjaitan; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In the Indonesian Criminal Procedure Code, Article of 184 explains 5 means ofevidence. The expert information is one of the legal evidence and was ranked numbertwo after the statements of the witnesses to be examined in the trial. The expertinformation is needed to make light of a case which may be required to be presented bythe presiding judge, prosekotor and the defendant. Based on this understanding, theauthor formulates three problems, namely: The first, how is the process of filing anexpert to testify in the trial of criminal cases in the District Court ?, second, what is thejudge’s consideration in accepting the expert presented by the parties in the criminalproceedings at the District Court?, and the third, how is the judge’s judgment indeciding a case based on expert information in the District Court?.This type of research can be classified in normative legal research (legalresearch) or also called research literature by examining secondary legal materials orresearch based on standard rules that have been recorded is also called bibliographyresearch, the type of data used is using secondary data consisting of primary,secondary and tertiary legal material. While the data collection used in this writing isthe method of literature review or documentary study, the data has been collected andthen processed bay way of selection, clarified systematically, logically and juridicallyqualitatively. The author draws a deductive conclusion, drawing the conclusions of thethings that are general to the things that are special.From the result of research and discussion it can be concluded that, First, theRegulation concerning the process of submission of an expert in the trial has beenregulated in the Criminal Procedure Code, whereby the presiding judge, publicprosecutor and defendant may propose an expert if deemed necessary to make light of acase. Second, an expert presented in Court should meet the requirements set forth in thedecree of Chief justice of the Supreme Court of the Republic of Indonesia, number:36/KMA/SK/II/2013 about Enabling Environment Case Management Guidelines inChapter VII. Third, consideration of the judge in deciding a case based on the expertinformation that is based on faith, when if the party who according to the judge'sconviction is not guilty then the expert statement submitted will be more considered.Keywords: Evidence-Expert Informant-Judge Consideration.